Occurrence of Scaptocoris castanea, perty, 1830 in cultivated pastures in Brazil - Costa, Ciniro; Forti, Luiz Carlos (Pesquisa Agropecuaria Brasileira, 1993)
The brown bug (Scaptocoris castanea, Perty 1830) is an insect of underground habits, which continuously suctions the juice through the roots leads the plants to emaciate, dry and die. It has not yet been described as pest in cultivated pastures in Brazil. Its occurrence has been observed in cultivated pastures of Cynodon dactylon cv. Coast cross and Brachiaria decumbens cv Brasilik and IPEAN in Red-Yellow Podzolic diytrophic soil originally covered by savannah vegetation, in Botucatu County, state of São Paulo.